Conditions suffisantes pour la représentation d’une fonction analytique par série des quasi-polynomes - Mechtijev, I. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. Г. Мехтиев. Достаточные условия разложимости аналитической функции в ряд квазиполиномов J. Mechtijevas. Analizinės funkcijos skleidimo kvazipolinomų eilute pakankamos sąlygos